Experimental studies of 1.5 – 1.6 μm high-power asymmetric-waveguide single-mode lasers. (June 2018) - Gorlachuk, P.V.; Ivanov, A.V.; Kurnosov, V.D.; Kurnosov, K.V.; Marmalyuk, A.A.; Romantsevich, V.I.; Simakov, V.A.; Chernov, R.V.
Abstract: The current – voltage, power – current, and spectral characteristics of high-power single-mode semiconductor lasers emitting at wavelengths of 1.5 – 1.6 μm are studied experimentally. It is shown that a laser with a cavity length of 1.6 mm and a mesa-stripe width of 3 μm mounted in a housing 11 mm in diameter may emit a power higher than 300 mW. Mounting of lasers on C-mounts makes it possible to achieve powers exceeding 400 mW. In the case of mounting in standard 14 pin DIL packages, the laser power at the exit of a single-mode fibre-optic cable (FOC) was no lower than 100 mW, which, taking into account 50 % losses upon radiation coupling into the FOC, corresponds to the laser diode power higher than 200 mW. It is shown that the differential resistance of a laser depends not only on the laser crystal length but also on the type of mounting (in copper housings 11 mm in diameter or on C-mounts). The dependences of the laser wavelength and spectral width on the pump current and ambient temperature are presented. The characteristic temperatures of laser diodes are determined.